Bone mineral density and associated genetic variants in high-level Caucasian marathon runners - Shane Heffernan (23rd European Congress of Sports Science, 2018)
INTRODUCTION:Endurance runners (except those who may have low energy availability) tend to have higher total and/or loading site-specific bone mineral density (BMD) in comparison with non-athletes, most likely due to the larger volume of exercise completed. A large genetic component also contributes to BMD, although little is known about which specific genes are involved, whether particular genotypes are sensitive to mechanical loading and the impact of such an interaction on BMD. This study investigated if high-level endurance runners possess enhanced BMD associated with an “advantageous” genetic predisposition, via a potential gene-physical activity interaction.METHODS:Age- and weight-adjusted total BMD (TBMD) and leg BMD (LBMD) measured via Dual-energy X-ray absorptiometry of 67 high-level Caucasian marathon runners (males < 2 h 45 min, n = 37; females < 3 15 min, n = 30) was compared with 40 male and 26 female non-athletes. LRP5 rs3736228, TNFRSF11B rs4355801, VDR rs2228570, WNT16 rs3801387 and AXIN1 rs9921222 variants were then investigated singularly, and collectively, as a total genotype score (TGS) via multivariate analysis of variance in a subgroup of this cohort (male runners n = 19, controls n = 26; female runners n = 17, controls n = 14). RESULTS:Male runners had higher TBMD (1.34 vs 1.28 g/cm2; P=0.02) and LBMD (1.53 vs 1.42 g/cm2; P=<0.01) than non-athletes. Female runners had higher LBMD than non-athletes (1.30 vs 1.22 g/cm2; P=0.02) but not TBMD (1.23 vs 1.18 g/cm2; P=0.22). An interaction (P=0.047) was observed between VDR rs2228570 genotype and group regarding LBMD in males: ff genotype runners had 0.02 g/cm2 higher LBMD than FF or Ff runners, but the FF genotype had the highest LBMD (1.45 g/cm2) amongst non-athletes. LBMD was also 0.12 g/cm2 higher in ff runners compared to ff non-athletes, whereas FF and Ff runners had 0.09 g/cm2 higher LBMD compared to their genotype-matched controls. No other interactions or variants, individually or collectively as part of a TGS, were associated with BMD (P≥0.11). CONCLUSION:High-level female runners possess higher LBMD but not TBMD in comparison with non-athletes whereas male runners possess both higher TBMD and LBMD than non-athletes. Consistent with prior literature, we observed higher BMD in VDR rs2228570 FF genotype in non-athletes, which may be due to increased biological activity associated with the F variant. However, our preliminary data suggest that the ff genotype may be associated with enhanced LBMD in male runners via a gene-environment interaction.